Numeracy Literacy Skills of Vocational School Students at NU Sunan Ampel Poncolkusumo in Solving PISA and TIMSS Problems - Ucik Fitri Handayani (Universitas Negeri Surabaya, 2025)
Students must possess numeracy as a basic skill. Numeracy questions are developed from PISA and TIMSS questions. This study aims to describe students' level of numeracy literacy when solving questions adapted from PISA and TIMSS. This descriptive qualitative study was conducted on 25 students in the 11th grade of TKJ FO at SMK NU Sunan Ampel Poncokusumo. Three students were selected as research subjects based on high, moderate, and low numeracy literacy categories. Data were collected through tests and interviews. The students were given three PISA and three TIMSS test questions aligned with numeracy literacy indicators: applying, interpreting, and analyzing. The results showed that students in each ability category performed differently on the numeracy literacy indicators. Students in the low and medium categories only met the analyzing indicator when answering PISA questions. Meanwhile, students in the low category were able to meet the applying and interpreting indicators on TIMSS questions, but not the analyzing indicator. Students in the medium category could meet the interpreting and analyzing indicators on TIMSS questions but not the applying indicator. Conversely, students in the high category met all numeracy literacy indicators when completing PISA and TIMSS questions.